"RURAL POVERTY REDUCTION THROUGH MICROFINANCE: A CASE STUDY OF CHHATTISGARH'S RURAL COMMUNITIES" (International Journal of Food and Nutritional Sciences, 2023)
This research investigates the effects of microfinance on reducing rural poverty in the varied communities of Chhattisgarh, India. It emphasizes the role of microfinance institutions (MFIs) in improving access to financial services and explores how these programs empower local residents, especially women, to participate in income-generating activities. Utilizing a mixed-methods approach that combines quantitative surveys with qualitative interviews, the study evaluates changes in income, employment opportunities, and overall quality of life for beneficiaries. The results suggest that microfinance has significantly enhanced financial inclusion, increased household incomes, and elevated the social status of marginalized groups. Nevertheless, challenges such as high-interest rates, over-indebtedness, and insufficient financial literacy remain prevalent. The study concludes with suggestions for policymakers and MFIs to improve the effectiveness of microfinance initiatives, promoting sustainable development and long-term poverty reduction in rural areas of Chhattisgarh.